Clinical study of anemia in rural school children of Mangalore, Karnataka, India - M. K., Mahroof; Khan, Shamshad Ahmed; Saldanha, Prakash (International Journal of Contemporary Pediatrics, 2019)
Background: The study was conducted to know the prevalence of anemia in rural school children located within 15km radius of Yenepoya Medical college hospital, Mangalore and to study the risk factors associated with anemia also to correlate the detection of anemia by clinical examination and by lab estimation of hemoglobin. Methods: A total of 550 children in the age group of 6-15 years were included in this study. Parental informed consent was obtained. A preplanner questionnaire was used to collect the health and socio demographic details. Blood was collected by venepuncture method and haemoglobin was determined by automated sysmex machine. Diagnosis of anemia was made according to WHO cut off value of Hb. Results: Out of 550 children 114(20.6%) were anemic. There was no significant difference between age and sex. Anemia was found to be more prevalent in children with h/o passing worms, undernourished, pica and low socio-economic status. Out of 550 children 174 children had conjunctival pallor on clinical examination. Among that 58 (33.3%) children had anemia on hemoglobin estimation. Majority of the children 116 (66.7%) who had pallor on clinical examination was found as non-anemic on hemoglobin estimation. On kappa co efficient, statistics showed that two examinations to detect anemia was 18.47 %, which indicates poor agreement. Conclusions: The overall prevalence of anemia among rural population is variable depending upon the region. Major factors which influence the prevalence of anemia were nutrition, socioeconomic status, pica and worm infestation. Clinical diagnosis by examination of pallor is poorly correlated by estimation of haemoglobin, hence anemia cannot be diagnosed by detection of pallor alone and it requires lab haemoglobin estimation to prevent wrong diagnosis of anemia.